Design and preliminary results of a 20-kW transcritical organic Rankine cycle with a screw expander for low-grade waste heat recovery. (5th January 2017) - Hsieh, Jui-Ching; Fu, Ben-Ran; Wang, Ta-Wei; Cheng, Yi; Lee, Yuh-Ren; Chang, Jen-Chieh
Highlights: A 20-kW TRC system using screw expander was studied for low-grade heat recovery. The experimentally average output power was 19.7 kW. The experimentally maximal system thermal efficiency was 5.7%. The isentropic efficiency of screw and pump were 57 and 58%, respectively. Abstract: This study experimentally examined a transcritical organic Rankine cycle (TRC) system with a screw expander and R218 as the working fluid in order to investigate system performance at heat source temperatures of 90–100 °C in both subcritical and supercritical states. Two centrifugal pumps in series were used to supply adequate operating pressure to the TRC system in the supercritical state of the working fluid. The operating pressures were controlled using the variable frequency drive (VFD) of the second pump. The efficiency of the expander and working fluid pumps peaked at the highest operating pressure in the supercritical state. The mass flow rate of the working fluid and the enthalpy difference between the inlet and outlet of the screw expander increased with operating pressure, resulting in an increase in output power. However, the output power was not significantly affected by the heat source temperature and the thermal efficiency slightly decreased with increasing heat source temperature. The present TRC system successfully converted the low-grade heat into approximately 20 kW of power. The thermal efficiency of the TRC system was 5.7%, 5.38%, and 5.28% for the heat source temperatures 90, 95, and 100 °C, respectively, with the VFD at 50 Hz.